2004
DOI: 10.1023/b:qure.0000021315.93360.8b
|View full text |Cite
|
Sign up to set email alerts
|

Assessing relationships between health-related quality of life and adherence to antiretroviral therapy

Abstract: HRQoL dimensions, notably cognitive functioning, financial status and medical care, are closely associated with antiretroviral therapy adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
42
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 49 publications
9
42
0
4
Order By: Relevance
“…Optimal adherence to medication regimen is a crucial factor to obtain desirable clinical outcomes in patients with HIV (1, 2), while suboptimal adherence results in poor clinical outcomes (3,4), poor quality of life (5,6), and mortality (7).…”
Section: Introductionmentioning
confidence: 99%
“…Optimal adherence to medication regimen is a crucial factor to obtain desirable clinical outcomes in patients with HIV (1, 2), while suboptimal adherence results in poor clinical outcomes (3,4), poor quality of life (5,6), and mortality (7).…”
Section: Introductionmentioning
confidence: 99%
“…Non adherence to antiretroviral therapy has been associated to diverse factors including patient related factors, health condition/disease, health care system/ health care team, therapy/treatment and socio-economic factors [20][21][22]. Reasons for non-adherence are multi factorial.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic literature review of 116 studies presents the conclusion that even though there is a positive trend in relation to adherence in various chronic illnesses and some areas of socioeconomic status, for example income, education and occupation, there is insufficient evidence about statistically significant associations between socioeconomic status and adherence among patients with HIV/AIDS (Falagas, 2008). On the contrary, other studies carried out with men and women reveal associations between a deficient financial situation and non-adherence (Carballo et al, 2004;Castro, 2005;Chesney, Chesney et al, 2000;Gifford et al, 2000;Glass, et al, 2006;Gordillo, 1999;Ickovics & Meade, 2002;Kleeberger et al, 2001). The truth is that poverty accounts for a higher probability of social disadvantages associated with risks to adherence.…”
Section: Discussing the Results Of The Study In Colombia -South Americamentioning
confidence: 96%
“…Allied to the other conditions which are typical of the lives of poor HIV-positive women, low education level can trigger a bad prognosis and the high risk of death from AIDS. With respect to income level, some authors have suggested that there are associations with adherence (Carballo et al, 2004;Ickovics & Meade, 2002), and propose that it would be reasonable to argue that attention to basic needs is more beneficial than direct attention to adherence. In particular, women of a low social position could receive social support for the satisfaction of their basic needs.…”
Section: Discussing the Results Of The Study In Colombia -South Americamentioning
confidence: 99%
See 1 more Smart Citation